Crossing boundaries and building bridges: the Anglican women's fellowship in post-apartheid South Africa - Gaitskell, Deborah (Journal of religion in Africa, 2004)
In the late 1960s, the South African Anglican Church set up a new women's organisation, the Anglican Women's Fellowship (AWF). With strong roots in the Cape and Natal, the AWF aimed to be more inclusive of all churchwomen than the international Mothers' Union (MU) where, at that time, membership was still closed to divorcees and unmarried mothers (...) Based on some documentary sources and participation in the fourday AWF Provincial Council of October 2002, this paper explores the changing composition, goals and ethos of AWF over its 35-year history. Comparisons with other churchwomen's organisations - the (black) Methodist Manyano and (white) Women's Auxiliary as well as the MU - will be drawn to highlight what is distinctive about AWF and its response to social change in contemporary South Africa. While the article concludes by providing a brief snapshot of theology and practise within the movement, the striking current role of Coloured women leaders as bridge-builders is particularly emphasised and the effective crossing of racial, social, language and age boundaries evaluated. (J Relig Afr/DÜI)